The Spatial Variation in Chlorophyte Community Composition From Coastal to Offshore Waters in a Subtropical Continental Shelf System - Lin, Yun-Chi; Chin, Chien-Pang; Chen, Wei-Ting; Huang, Ching-Ting; Gong, Gwo-Ching; Chiang, Kuo-Ping; Chen, Xin-Bei (Frontiers in Marine Science, 2022)
Globally, the continental shelf occupies less than 10% of the total sea surface, but supports substantial primary production and fisheries. Photosynthetic picoeukaryotes (PPE) are important primary producers in marine ecosystems, and chlorophytes make a significant contribution to PPE abundance. Although the distribution of chlorophytes has been widely studied, little is known about how their community composition varies along the coastal-offshore gradient in subtropical continental shelf waters. To better understand their spatial variations, we employed metabarcoding data of 18S rRNA V4 gene to examine chlorophyte composition within the surface and deep chlorophyll maximum (DCM) layers over the continental shelf in the East China Sea (ECS) with high-resolution sampling. Our results indicate a higher chlorophyte diversity in the surface layer than in the DCM. In addition, we found that chlorophytes in oligotrophic Kuroshio surface water were the most diverse, with a higher percentage of Chloropicophyceae, prasinophyte clade V, prasinophyte clade IX, Palmophyllophyceae and Chlorodendrophyceae. In more eutrophic waters along the coast and within the DCM layer, chlorophytes were dominated by Mamiellophyceae. A significant spatial variation in community composition occurred along the nutrient gradient in the subtropical continental shelf ecosystem, varying from Mamiellophyceae-dominant in coastal water to Chloropicophyceae-dominant in offshore water. Furthermore, at a low saline coastal station, which had the lowest chlorophyte diversity, Picochlorum (Trebouxiophyceae) was dominant. Overall, chlorophyte diversity was positively correlated with temperature, and negatively correlated with silicate concentration. This study revealed that terrestrial input into continental systems influences chlorophyte diversity in the subtropical northwestern Pacific Ocean.